(untitled) (Research, Society and Development, 2021)
The sexual precocity of heifers of a breeding program in the state of Acre, Brazil, was evaluated from January 2018 to February 2019. The herd included 184 Nellore heifers of 11 to 14 months of age, with mean body weight of 280.17 kg at the time of cyclicity induction (CI) and mean body weight gain of 0.6 kg day-1. The heifers were weighed, subjected to the CI protocol, and classified into the Categories A (uterine tone and ovarian cyclicity), B (uterine tone or ovarian cyclicity), and C (ovarian acyclicity and no uterine tone); then, they were subjected to estrus synchronization focused on fixed-time artificial insemination, with pregnancy diagnosis performed after 30 days. They were also subjected to carcass ultrasound to assess the ribeye area (REA) and carcass finishing level (CFL). The variables evaluated were: REA, CFL, body weight, selection index, age, and pregnancy rate. Pearson’s correlation was used for the variables body weight, REA, CFL, selection index, and age. The pregnancy rate found was 42%, which was similar (p>0.05) in all categories. Pregnant and non-pregnant heifers presented similar (p>0.05) REA and CFL. The categories presented differences (p<0.05) for age and body weight at CI, and no differences (p>0.05) in REA and CFL. The bulls used presented no difference in genetic potential. The Nellore heifers from the study herd have high sexual precocity, classified as super-precocious and precocious. Heifers that present higher body weight tended to be more precocious, denoting the importance of this characteristic in production systems.